Shopping Spaces and the Urban Landscape in Early Modern Amsterdam, 1550-1850 - Lesger, Cl. (Clé) (Amsterdam studies in the Dutch golden age., 2020)
In this study, the appearance and location of shops in Amsterdam during the early modern period is linked to major changes in the urban economy, the size and socio-spatial distribution of its population, and the structure of the urban grid. Not only is there ample attention for the spatial distribution of shops across the urban landscape, but for the first time it is also accurately charted what the exterior and interior of Amsterdam shops actually looked like and how they changed in the course of the centuries. Partly as a result of this, it has proved possible to give an impression of the ways in which retailers and customers interacted.